Design and implementation: an open and reconfigurable router architecture with different network system supported - Ze-xin LU; Xiao-zhe ZHANG; Shi-cong MA; Bao-sheng WANG (Tongxin xuebao)
Targeted the problems of current network device on supporting reconfigurable functions and multiple new network architectures, a novel open and reconfigurable router architecture was proposed to support the coexistence of multiple network architecture in one router. virtualization and hardware partition technology were used to divide a router hardware into multiple logical router instances, assured logical router instances that did not effect each other.